2018
DOI: 10.20473/j.djmkg.v51.i2.p76-80
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic traumatic ulcer mimicking oral squamous cell carcinoma on the tongue

Abstract: Background: Traumatic ulcers represent the most common oral mucosal lesions that can be differentiated from oral squamous cell carcinoma (OSCC) by their clinical appearance. From a clinical perspective, OSCC may resemble a chronic traumatic ulcer (CTU) because the base of the CTU that is healing is filled with reddish-pink granulated tissue, similar to that in OSCC. Purpose: The aim of this case report is to provide information about the oral management of a CTU case that imitates OSCC. Case: A 30-year old fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 13 publications
0
18
0
6
Order By: Relevance
“…Another study also found that topical anesthetics were the predominant drug of choice in the management of traumatic ulcer (Choudhury, 2015;Nelonda and Setiadhi, 2018).…”
Section: Resultsmentioning
confidence: 97%
“…Another study also found that topical anesthetics were the predominant drug of choice in the management of traumatic ulcer (Choudhury, 2015;Nelonda and Setiadhi, 2018).…”
Section: Resultsmentioning
confidence: 97%
“…The clinical manifestations after 5 weeks was ulcer, 2x2 cm in size, with indurated edges, with necrotic tissue in the middle with hard palpations giving a strong suspicion that the lesion was OSCC. 4 As a dentist it was necessary to ascertain the ulcer lesions resembling a malignancy and to consider the patient's work to be able to predict a diagnosis of the lesion. The ulcer was treated with 0.2% chlorehexidine digluconate as an antiseptic with a longlasting antibacterial activity and with broad-spectrum bactericidal that can reduce plaque, inflammation and bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…[2,3] An OSCC is the most common persistent ulcer affecting the oral cavity which encompasses 90-95% of oral cancers. [4]It generally affects men aged over 50, most of them with a history or risk factors of high tobacco smoking, alcohol consumption, and smokeless tobacco use… [2,5] OSCC has various clinical presentations and may, at times, be ambiguous. Early lesions are often asymptomatic and can often be misdiagnosed as other inflammatory lesions in the oral cavity, a fact that can cause the patient to delay seeking treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Early lesions are often asymptomatic and can often be misdiagnosed as other inflammatory lesions in the oral cavity, a fact that can cause the patient to delay seeking treatment. [4] An early OSCC may be a shallow ulcer with a velvety red base and a firm, raised border. A healing chronic traumatic ulcer can resemble an early OSCC because its base may be filled with reddish-pink granulation tissue.…”
Section: Introductionmentioning
confidence: 99%